(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This article explores methods for the effective utilization of tourist resources to promote sustainable tourism development in the Samarkand region of Uzbekistan. Samarkand, a UNESCO World Heritage site, is renowned for its rich cultural heritage and historical significance along the Silk Road. The study analyzes strategies to balance economic growth, environmental preservation, and socio-cultural integrity through sustainable tourism practices. Using a SWOT analysis enhanced by the Analytic Hierarchy Process (AHP), the research identifies key opportunities and challenges in leveraging Samarkand’s tourism potential. Results highlight the importance of community engagement, eco-tourism initiatives, and the establishment of free tourist zones to foster sustainable development. Recommendations include policy interventions, stakeholder collaboration, and investment in green infrastructure to ensure long-term sustainability.